Efficacy and Safety of BCG Revaccination With M. bovis BCG Moscow to Prevent COVID-19 Infection in Health Care Workers: A Randomized Phase II Clinical Trial - dos Anjos, Laura Raniere Borges; da Costa, Adeliane Castro; Cardoso, Amanda da Rocha Oliveira; Guimarães, Rafael Alves; Rodrigues, Roberta Luiza; Ribeiro, Kaio Mota; Borges, Kellen Christina Malheiros; Carvalho, Ana Carolina de Oliveira; Dias, Carla Iré Schnier; Rezende, Aline de Oliveira; Souza, Carine de Castro; Ferreira, Renato Rodney Mota; et al. (Frontiers in Immunology, 2022)
The Bacillus Calmette-Guérin (BCG) vaccine, which is widely used to protect children against tuberculosis, can also improve immune response against viral infections. This unicentric, randomized-controlled clinical trial assessed the efficacy and safety of revaccination with BCG Moscow in reducing the positivity and symptoms of COVID-19 in health care workers (HCWs) during the COVID-19 pandemic. HCWs who had negative COVID-19 IgM and IgG and who dedicated at least eight hours per week in facilities that attended to individuals suspected of having COVID-19 were included in the study and were followed for 7, 15, 30, 60, and 180 days by telemedicine. The HCWs were randomly allocated to a revaccinated with BCG group, which received the BCG vaccine, or an unvaccinated group. Revaccination with BCG Moscow was found to be safe, and its efficacy ranged from 30.0% (95.0%CI -78.0 to 72.0%) to 31.0% (95.0%CI -74.0 to 74.0%). Mycobacterium bovis BCG Moscow did not induce NK cell activation at 15–20 days post-revaccination. As hypothesized, revaccination with BCG Moscow was associated with a lower incidence of COVID-19 positivity, though the results did not reach statistical significance. Further studies should be carried out to assess whether revaccination with BCG is able to protect HCWs against COVID-19. The protocol of this clinical trial was registered on August 5th, 2020, at REBEC (Registro Brasileiro de Ensaios Clínicos, RBR-4kjqtg - ensaiosclinicos.gov.br/rg/RBR-4kjqtg/1) and the WHO (# U1111-1256-3892). The clinical trial protocol was approved by the Comissão Nacional de ética de pesquisa- CONEP (CAAE 31783720.0.0000.5078).